Evaluasi Penerapan Balanced Scorecard (PBS) Dalam Manajemen Madrasah - M. Syukri Rizki Hamdalah; M. Dimas Aditya; Ubaidillah Ubaidillah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the application of the Balanced Scorecard (BSC) in the framework of madrasah strategic management with an integrated Islamic approach. The main focus of the research is to examine how the five BSC perspectives of finance, customers, internal processes, learning and growth, and integration of Islamic values can be contextually adapted in the performance evaluation system of Madrasah Al-Washliyah Tembung. This research uses a descriptive qualitative approach with survey methods, observation, and in-depth interviews with leaders, teachers, and education personnel. The results showed that the application of the four classical BSC perspectives had begun to be implemented but still faced obstacles in the aspects of digitization, systematization of indicators, and strengthening a data-based work culture. The main innovation in this study is the addition of a fifth perspective, namely the integration of Islamic values, which includes sincerity, trustworthiness, and social responsibility in the madrasah performance system. These values have been internalized in institutional practices, although they have not been fully standardized as formal indicators. The conclusion of this study confirms that the development of an Islamic value-based BSC model can contextually strengthen madrasah performance, not only in terms of efficiency and accountability, but also in terms of spirituality and morality. Thus, BSC developed in a sharia-compliant manner is a strategic alternative in realizing superior and sustainable madrasah governance.